SINO-ARABIC SCRIPT AND ARCHITECTURAL INSCRIPTIONS IN XI’AN GREAT MOSQUE, CHINA - Dilmi, Djamel (Journal of Islamic Architecture, 2014)
The Islamic art have played a significant role in the development of Muslim Chinese community in China, it wasdeveloped through time in response to cultural needs of the minority Muslim groups in China. The Islamiccalligraphy was widely used in architecture, especially in interior and exterior decoration of mosques andother religious buildings. The aim of this study is to interpret the Islamic art and architecture in China throughapplication of Sino-Arabic script on mosques and crafts produced by Muslim minority in China in relation to theIslamic civilization and Chinese civilization, in order to suggest some guidelines for the preservation of thisforgotten Islamic heritage. To achieve the aim of this paper the Sino-Arabic inscriptions will be examined inorder to determine their characteristics and the nature of the effects to which they have been subjected. Abroad range of information was collected from various sources and through a field survey that was carried outin Xi’an Great Mosque in China. The collected information from field work will be analyzed with particularregard to the special character of Chinese Islamic art and architecture. This study is an attempt to addressthe important topic of Islamic calligraphy and its application on architectural buildings in China as part ofissues of Islamic architectural heritage and its integration with local tradition that have been occurred in theMuslim world and it is hoped that it is going to be a significant contribution to the subject of Islamic art andarchitecture in China as well as revival and preservation of this forgotten heritage. Detailed conclusion will bearrived at the end and specific suggestions are intended to assist in examining the topic in depth and helping indeveloping guidelines for regional expansion and adaptation of Islamic art and architecture with localenvironmental condition to contribute more for the future of Muslim heritage and civilization.